Challenges in Achieving SDG 2 - Zero Hunger in Bangladesh: An Analytical Study on Food Certainty in Bangladesh from Zakat Perspective - Abu Hamid Aziz; Moniruzzaman Moniruzzaman (International Journal of Zakat, 2023)
The Sustainable Development Goals (SDGs) were adopted by the United Nations (UN) on 25 September 2015. It consists of 17 interconnected goals intended to be achieved over the next 8 years (2030). Most of the goals are present in Bangladesh and goal number two “end hunger, achieve food security and improved nutrition and promote sustainable agriculture” is one of them. However, the current progress scenario towards achieving SDG 2 in the country is unsatisfactory due to some obstacles. As the world's third largest Muslim country, Zakat has huge potential as a source of revenue in Bangladesh. Undoubtedly, Zakat is one of the most important tools of Islamic finance that can play a vital role in alleviating hunger in the country. The study aims to identify the challenges faced by Bangladesh to acquire goal number 2 of SDG and particularly analyse the impact of zakat on improving the food safety status in the country which will facilitate the path towards achieving SDG 2 – Zero Hunger. This study is expected to contribute primarily to the government and zakat management institutions of Bangladesh to optimize the feasibility and utilization of the zakat mechanism. Keywords: Challenges, SDGs, Zero Hunger, Food Certainty, Bangladesh, Zakat.